Analisis Penerimaan SIREKAP Pemilu 2024 dengan Metode UTAUT dan TTF (Studi Kasus : Paal Merah) - Calista Devi, Anisa; Sharipuddin; Joni Devitra (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2025)
This study analyzes the acceptance and use of the Sistem Informasi Rekapitulasi (SIREKAP) application in the 2024 Simultaneous Election in Indonesia, with a focus on Paal Merah District, Jambi City. The main objective of this research is to evaluate the factors influencing SIREKAP acceptance using the Unified Theory of Acceptance and Use of Technology (UTAUT) and Task Technology Fit (TTF) models. Based on data analysis from 254 respondents, the study found that Performance Expectancy positively influences the intention to use the application, while factors such as Effort Expectancy and Social Influence have no significant effect. Additionally, Task Technology Fit plays a significant role in improving performance and the usage of the SIREKAP application. These findings provide insights into the factors that need to be considered when implementing information technology in the election sector, as well as the importance of task-technology alignment in influencing the acceptance of applications.